Evaluation of Block Learning Innovation Program in MAN 2 Lubuk Pakam - Ahmad Mukhlasin; Syafaruddin Syafaruddin (EDUTEC : Journal of Education And Technology, 2021)
The purpose of this paper is to describe the implementation of the evaluation of the Block Learning learning innovation program at MAN 2 Lubuk Pakam. This research method is qualitative research and uses an evaluation model that is in accordance with the theme adopted, namely the CSE-UCLA Evaluation Model with five stages carried out in the evaluation, namely planning, development, implementation, results and impact. The results of this study are 1. The effectiveness of block learning learning innovations at MAN 2 Lubuk Pakam really helps the learning process, not only material that is easy to understand, from an economic perspective it also helps parents of students, this innovation is also very effectively applied in MAN 2 Lubuk Pakam , because the learning carried out produces positive things where students understand the material better, and it is better than online learning with Google Class Room or others, in the previous semester. 2. Evaluation of the block learning innovation program at MAN 2 Lubuk Pakam, namely: a. the planning carried out to start the Block Learning program has shown that the process has been carried out well because it involves many people and has determined several things that are needed for the implementation of the Block Learning program well in the future b. the development of the Block Learning learning innovation program was carried out well where the development was carried out in the even semester to the implementation in the previous semester, namely the odd semester regarding the effectiveness of the time for collecting teacher material in the field of study, thus this program will continue to improve if it continues to be developed in the future. c. the implementation of the implementation of block learning shows that the implementation is very structured, it can be seen that the sequence from the beginning from the formulation of the material to the distribution of the learning blocks and the collection of tasks carried out by the students is carried out in an orderly manner. d. the results of the program are very significant and include all the goals at the beginning of program planning where to anticipate declining learning in the previous semester, and to help the economy of parents who were hit by the covid 19 pandemic outbreak, the things that were planned had been implemented properly and resulted in results. amazing. and e. This Block Learning does not have a follow-up for the future, because this program is only for dealing with learning during a pandemic that requires PJJ (Distance Learning)..